Compounds Isolated from the Leaf of Sanchezia nobilis Hook.f. - Loi, Vu Duc; Xuan, Bui Thi; May, Vu Thi; Thuy, Tran Thi Bich; Dung, Hoang Viet; Huong, Do Thi Mai (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1DO - 10.25073/2588-1132/vnumps.4110, 2018)
The ethyl acetate fraction of the leaf of Sanchezia nobilis  Hook.f. (collected in Nam Dinh province) isolated three compounds (1-3) by chromatographic methods. Their structures were elucidated by spectroscopic methods, including MS and NMR. These compounds were identified as: 9-methoxycanthin-6-one (1); 9-hydroxyheterogorgiolid (2); and O-methyl furodysinin lactone (3). These compounds were, for the first time, isolated from the leaf of Sanchezia nobilis Hook.f. Keywords 9-methoxycanthin-6-one, 9-hydroxyheterogorgiolide, O-methyl furodysinin lactone. References Ellah A. E. A., Mohamed K. M., Backheet E. Y., et al. (2013), "Matsutake alcohol glycosides from Sanchezia nobilis", Chemistry of Natural Compounds, 48(6), pp. 930-933. [2] Nguyễn Tiến Bân (2005), Danh lục các loài thực vật Việt Nam, tập 3, Nhà xuất bản Nông nghiệp, trang 272-273. [3] Phạm Hoàng Hộ (2000), Cây cỏ Việt Nam, tập 3, Nhà xuất bản Trẻ, tr.39. [4] Đỗ Tất Lợi (2001). Những cây thuốc và vị thuốc Việt Nam. NXB Y học, tr. 518-520. [5] Paydar M., Wong Y. L., Moharam B. A., et al. (2013), "In vitro anti-oxidant and anti-cancer activity of methanolic extract from Sanchezia speciosa leaves", Pakistan Journal of Biological Sciences, 16(20), p. 1212. [6] Rafshanjani M., Parvin S., Kader M., et al. (2014), "In vitro antibacterial, antifungal and insecticidal activities of ethanolic extract and its fractionates of ia speciosa Hook. f", Int Res J Pharm, 5(9), pp. 717-720. [7] Parvin S., Rafshanjani M. A. S., Kader M. A., et al. (2015), "Preliminary phytochemical screening and cytotoxic potentials from leaves of Sanchezia speciosa Hook. f", International Journal of Advances in Scientific Research, 1(3), pp. 145-150. [8] Kevin Hung, Xirui Hu and Thomas J. Maimone (2005), Total synthesis of complex terpenoids employing radical cascade processes, Nat. Prod. Rep., 22, 465. [9] Kensuke Ohishi, Kazufumi Toume, Midori A. Arai, Takashi Koyano, Thaworn Kowithayakorn, Takamasa Mizoguchi, Motoyuki Itoh, and Masami Ishibashi (2015), 9-Hydroxycanthin-6-one, a β-Carboline Alkaloid from Eurycoma longifolia, Is the First Wnt Signal Inhibitor through Activation of Glycogen Synthase Kinase 3β without Depending on Casein Kinase 1α. J. Nat. Prod., 78 (5), pp 1139–1146. [10] Sofa Fajriah, Muhammad Hanafl, Atiek Sumiati , and Ngadiman (2010), isolation and identification of 9-methoxycanthin-6-on from Eurycoma longifolia roots, Fitoterapia 81, (7), pp. 669-679. [11] Andrew M. Piggott and Peter Karuso (2005), 9-Hydroxyfurodysinin-O-ethyl Lactone: A New SesquiterpeneIsolated from the Tropical Marine Sponge Dysidea arenaria,Molecules, 10, pp.1295-1297.